International air travel and the demand for a direct polar air link between Argentina and Australia - Smith, MC (1981)
The principal aim of the study has been to examine the effects on travel to and from South America of the introduction of a new direct air link to Argentina. It is proposed that this new air route from Melbourne to Buenos Aires should follow a great circle route across the Antarctic so as to shorten the distance between the two centres from approximately 10,000 miles to approximately 7,200 miles. In achieving this result the study implicitly has two major sections. The first of these involves the estimation of factors affecting travel to and from Australia. This initially involves recognition of some of tiie main features and problems encountered in demand modelling techniques. Travel is estimated in terms of over- . seas visitors coming to Australia and Australian residents travelling overseas using 1980 cross-section data. Having estimated the magnitude of various factors affecting travel these results are then applied to the South American countries most affected by the direct air link. Application of the model para-meters enable forecasts to be made of the likely generation of travel both to and from Australia with the shortened, direct air route. Chapter two undertakes a review of travel demand modelling techniques. As well as providing a discussion of various types of demand studies carried out it emphasises some of the more important issues considered to apply to the new direct air route. The gravity model approach is introduced and then extended to techniques usedin city-pair demand modelling. The purpose of this discussion is to draw out possible implications for model coefficients . of increased travel distance and also to show the role of various impedance factors to travel. This:serves as a foundation for the discussion of factors affecting international air travel demand. The area of international air travel demand modelling focuses primarily on cross-section. data models. However, some of the more pertinent time series approaches are discussed to clarify important points. One such issue is the ...